Factors partitioning physical frailty in people aging with HIV: A classification and regression tree approach. Issue 7 (1st February 2022) - Inceer, Mehmet; Brouillette, Marie‐J.; Fellows, Lesley K.; Morais, José A.; Harris, Marianne; Smaill, Fiona; Smith, Graham; Thomas, Réjean; Mayo, Nancy E.
Abstract: Objective: To estimate the extent to which comorbidity and lifestyle factors were associated with physical frailty in middle‐aged and older Canadians living with HIV. Design: Cross‐sectional analysis of 856 participants from the Canadian Positive Brain Health Now cohort. Methods: The frailty indicator phenotype was adapted from Fried's criteria using self‐report items. Univariate logistic regression and classification and regression tree (CaRT) models were used to identify the most relevant independent contributors to frailty. Results: In all, 100 men (14.0%) and 26 women (19.7%) were identified as frail (≥ 3/5 criteria) for an overall prevalence of 15.2%. Nine comorbidities showed an influential association with frailty. The most influential comorbidities were hypothyroidism [odds ratio (OR) = 2.55, 95% confidence interval (CI): 1.29–5.03] and arthritis (OR = 2.54, 95% CI: 1.58–4.09). Additionally, tobacco (OR = 1.79, 95% CI: 1.05–3.04) showed an association. Any level of alcohol consumption showed a protective effect for frailty. The CaRT model showed nine pathways that led to frailty. Arthritis was the most discriminatory variable followed by alcohol, hypothyroidism, tobacco, cancer, cannabis, liver disease, kidney disease, osteoporosis, lung disease and peripheral vascular disease. The prevalence of physical frailty for people with arthritis was 27.4%; with additional cancer or tobacco and alcohol the prevalence rates were 47.1% and 46.1%, respectively. The protective effect of alcohol consumption evident in the univariate model appeared again in the CaRT model, but this effect varied. Cognitive frailty (19.5% overall) and emotional frailty (37.9% overall) were higher than the prevalence of physical frailty. Conclusions: Specific comorbidities and tobacco use were implicated in frailty, suggesting that it is comorbidities causing frailty. However, some frailty still appears to be HIV‐related. The higher prevalence of cognitive and emotional frailty highlights the fact that physical frailty should not be the only focus in HIV.